Repurposing pentamidine for cancer immunotherapy by targeting the PD1/PD-L1 immune checkpoint - Gu, Tingxuan; Tian, Xueli; Wang, Yuanyuan; Yang, Wenqian; Li, Wenwen; Song, Mengqiu; Zhao, Ran; Wang, Mengqiao; Gao, Quanli; Li, Tiepeng; Zhang, Chengjuan; Kundu, Joydeb Kumar; et al. (Frontiers in Immunology, 2023)
Immunotherapy has emerged as an effective therapeutic approach to several cancer types. The reinvigoration of tumor-infiltrating lymphocyte-mediated immune responses via the blockade of immune checkpoint markers, such as program cell death-1 (PD-1) or its cognate ligand PD-L1, has been the basis for developing clinically effective anticancer therapies. We identified pentamidine, an FDA-approved antimicrobial agent, as a small-molecule antagonist of PD-L1. Pentamidine enhanced T-cell-mediated cytotoxicity against various cancer cells in vitro by increasing the secretion of IFN-γ, TNF-α, perforin, and granzyme B in the culture medium. Pentamidine promoted T-cell activation by blocking the PD-1/PD-L1 interaction. In vivo administration of pentamidine attenuated the tumor growth and prolonged the survival of tumor-bearing mice in PD-L1 humanized murine tumor cell allograft models. Histological analysis of tumor tissues showed an increased number of tumor-infiltrating lymphocytes in tissues derived from pentamidine-treated mice. In summary, our study suggests that pentamidine holds the potential to be repurposed as a novel PD-L1 antagonist that may overcome the limitations of monoclonal antibody therapy and can emerge as a small molecule cancer immunotherapy.